Reporting of Gross Written Premium in the Selected European Countries - Jiřina Bokšová; Monika Randáková (European Financial and Accounting Journal, 2013)
The goal of this article is to compare the content of gross written premium in the selected European countries. The subject of insurance companies is to provide insurance protection based on commercial principles. All changes in the society are directly reflected in the insurance activity. New risks appear and therefore new insurance products appear as well. Insurance activities are divided into non-life insurance, life insurance, and in recent years increase also a share of life unit linked insurance. Yield in the form of gross written premium arises to the insurance company under insurance contracts and then must be adjusted about so called unearned premiums. The article deals with outputs of research of gross written premium in particular insurance companies in different states of Central and Eastern Europe.
Keywords: M41; 650; Insurance; Gross written premium; Non-life insurance; Life insurance; Unit linked